Rancang Bangun Aplikasi Ticketing System IT Support Berbasis Web Menggunakan Framework Laravel pada PT. LMA Highway Konsorsium - Legowo, Galih; Utomo, Yudo Bismo; Anam, Moh. Syaiful (Teknik Komputer Fakultas Teknik Universitas Islam Kadiri (UNISKA), 2026)
Technical issue reporting in IT Support divisions often becomes problematic when the process is still carried out conventionally through instant messages, phone calls, or direct verbal reports. This condition makes reports difficult to track, vulnerable to being overlooked, and poorly documented in terms of maintenance history. This study aims to design and develop a web-based IT Support ticketing system for PT. LMA Highway Konsorsium using the Laravel framework. The development method follows the System Development Life Cycle (SDLC) with the Waterfall model, consisting of requirement analysis, design, implementation, testing, and maintenance. The developed system provides two main access roles: User as the employee who submits reports and Admin as the IT Support technician who manages tickets. The main features include user authentication, ticket submission, status tracking through Pending, Processing, and Completed stages, issue categorization, priority classification, user management, profile updates, and interactive notifications using SweetAlert2. The implementation results indicate that the application centralizes technical issue reporting, improves communication between employees and technicians, and provides a structured maintenance history to support IT Support service evaluation. Keywords: IT Support, Ticketing System, Helpdesk, Laravel, Technical Issue Reporting.